Mitochondrial Biogenesis Induced by Exercise and Nutrients: Implication for Performance and Health Benefits - Kazumi Masuda; Thomas Jue; Ronald D. Ray Hamidie (Indonesian Journal of Science and Technology, 2017)
The skeletal muscle occupies about 40% of body mass, one of the largest organs in the body, and it has great plasticity in response to physiological stressors and then alters the contractile and metabolic properties of the muscles. Therefore, healthy status of muscle affects health status of whole body. Mitochondria are abundantly present in mammalian muscle cells, known as the power plants of the cell to generate adenosine triphosphate (ATP) with oxygen. The muscle health depends on the mitochondrial function. In aging and some of metabolic disease states, the mitochondrial function is defected. Some parts of this defect result from lower physical activity and nutritional status. The exercise is well-known as a major strategy to induce mitochondrial biogenesis and upregulation of the mitochondrial function. Recently some nutrients are also suggested as ligands for transcription of the mitochondrial proteins. We also recently found insight of protein interaction with mitochondria that will possibly augment mitochondrial respiratory potential. The present review article introduces some recent research evidences relating to mitochondrial quality control, mitochondrial biogenesis mediated by both exercise and nutrients and an interaction of protein with mitochondria to facilitate mitochondrial respiration.